Clinical outcomes of magnetic activated sperm sorting in infertile men candidate for ICSI. (3rd April 2019) - Ziarati, Niloofar; Tavalaee, Marziyeh; Bahadorani, Mehrnoosh; Nasr Esfahani, Mohammad Hossein
Abstract: Magnetic activated cell sorting (MACS) with annexin V microbeads deselected apoptotic sperm with externalized phosphatidylserine (PS) residues on their surface and decrease chance of such sperm to be inseminated. Therefore, the aim of this study was to evaluate efficiency of MACS procedure in a prospective randomized trial. Sixty-two semen samples were allocated into two groups and processed according to: (i) a combination of MACS with density gradient centrifugation (MACS–DGC) as study group ( N  = 29); and (ii) DGC alone as a control group ( N  = 33). Fertilization, embryo quality, pregnancy and implantation rates were compared between the two groups. Although, no significant difference was observed in fertilization rates between the two groups, the percentage of high-quality embryos, pregnancy and implantation rates was significantly higher in the MACS–DGC group compared to DGC alone. Therefore, MACS may help to select the most fertile sperm and improve clinical outcomes of intra-cytoplasmic sperm injection (ICSI).